Terminus of the Wild Goose Railroad at Anvil Creek, Alaska, approximately 1901. - Hegg, Eric A., 1867-1948 (1901)
Caption on image: "Wild Goose R.R. Nome, Alaska" Original photograph by Eric A. Hegg 1609; copied by Webster and Stevens 14.A